Measuring the General and Specific Domains of Self-Esteem: The Short-form of the State Self-Esteem Scale - Brito, Tátila Rayane de Sampaio (2022)
Self-esteem is a crucial human nature feature for understanding the social dimensions of individuals’ self-concept. One of its characteristics is peoples’ malleability to adapt to social contexts, that is, the state self-esteem (SSE). Individuals express SES in three different factors: performance; social success; and physical appearance. Along with three studies, we present evidence of validity of the Short-Form of State Self-Esteem Scale (SSES-S) that measures contextual fluctuations in individuals’ self-esteem. In Study 1 (N = 300), we found that the structure of the SSES-S was organized into three correlated factors that exhibited convergent-discriminant validity with measures of trait self-esteem and human values. In Study 2 (N = 281), confirmatory factor analysis indicated that a bifactor measurement model better fit the description of the factorial structure of the SSES-S, which also showed incremental validity concerning trait self-esteem for predicting one criterion. In Study 3 (N = 160), we experimentally manipulated contextual information about self-achievement and showed that the SSES-S is sensitive enough to detect transient fluctuations in self-esteem, especially in the achievement factor. We discussed the limitations and scope of the SSES-S, as its specific focus on measuring undergraduate students’ state self-esteem and its implications distinguishing the general and particular domains of this construct.